Optimal integration of renewable energy in refinery hydrogen management systems: Energy storage and direct utilization - Zhou, Yingqian; Wang, Yufei; Yang, Minbo (Energy conversion and management, 2024)
•Introducing renewable energy into refinery hydrogen management systems.•Renewable energy used for green hydrogen production and hydrogen compression to satisfy direct hydrogen demands.•Reducing the number of energy conversions in energy storage and utilization.•Analyzing the perspectives of renewable energy for hydrogen management systems. Renewable energy generally requires energy storage systems for peak shaving and valley filling due to wide distribution and strong intermittency. Most energy storage and utilization methods involve multiple energy conversion steps, leading to low energy utilization efficiencies. This work develops a novel system that integrates refinery hydrogen management system with renewable energy storage and direct utilization that enhances the energy utilization efficiencies. A superstructure is established considering wind power for green hydrogen production and hydrogen compression to satisfy hydrogen demands directly. A nonconvex mixed-integer nonlinear programming (MINLP) model is formulated to optimize the integrated system, and a hierarchical algorithm is proposed to effectively solve the optimization model. The case studies indicate that the renewable energy-refinery hydrogen management system can reduce the total annual cost by 21.21% and 13.49% for abandoned and normal wind power prices, respectively. With the wind power price reduced in the future, the total annual cost can be reduced further, 15.09% in the 2035 case and 16.61% in the 2050 case. Besides, the wind power price greatly affects the utilization rate, which increases from 57.67% in the 2025 case to 90.11% in the 2050 case. In comparison, wind power used for hydrogen compression demonstrates economic advantages over green hydrogen production. Technological innovation is vital for green hydrogen production to improve the economy.